(untitled) (CIPEEX, 2025)
This article addresses the design and implementation of a modular management system aimed at easy customization and functionality adaptation to serve various market segments. The system was designed with a modular architecture, allowing users to activate, deactivate, or replace modules according to their specific needs, without compromising the integrity of the codebase. This modular model enables the software to be adjusted quickly and efficiently, reducing the need for interventions from the development team, while providing a more flexible and adaptable product. The system’s architecture was based on patterns such as plugin architecture and microservices, allowing each module to function independently, promoting scalability and maintenance. This structure ensures that new features can be integrated simply, without negatively affecting the system’s performance or stability. The article also highlights the importance of an intuitive and flexible user interface, designed to allow users with little technical knowledge to configure and customize the modules according to their operational needs, whether in corporate environments or small businesses. The study results indicate that adopting a modular approach facilitates system customization while significantly reducing maintenance and update costs. The scalability provided by the modularity and microservices architecture makes the system highly adaptable to different market scenarios, ensuring greater longevity and efficiency. It is concluded that a modular management system, focused on customization, represents an innovative and effective solution to meet users’ dynamic demands, offering flexibility and greater control over functionalities.